The Effectiveness of Cooperative Learning in the Class of Inferential Statistics - Suhaida Abdullah (IJORER : International Journal of Recent Educational Research, 2021)
The challenge in teaching statistics encompasses student motivation, mathematical anxiety, and student understanding. It needs an approach of education that encourages curiosity and leads to the engagement and comprehension of students. Cooperative learning is one of the teaching approaches that can be defined as learning with small groups of friends and implementing what they have learned in a lecture to achieve the same objective. Employing cooperative learning in the class of inferential statistics and assessing the efficacy of this approach is the aim of this study. The efficiency of the approach is determined based on the student's perception, the lecture’s observation, and the student's performance. The results showed that students more prefer to learn in a group during the course. While, based on the lecture’s observation, letting students sit in a group engages students positively during their lessons. After the implementation of cooperative learning, the student performance also exhibited improvement. Hence, it is tolerable to conclude that cooperative learning is efficient in increasing student engagement and performance.